The Use of Text Twist Game through Mind-Mapping to Improve Students’ Vocabulary - Fadhilah, Nur; Muhayyang, Maemuna; Aeni, Nur (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
The research aimed to determine whether or not using mind mapping with the Text Twist game improves students' vocabulary. Pre-experimental design was employed by the researcher. The current research focuses on a pre-test and post-test for a single group that consists of 40 multiple-choice vocabulary questions. There were 143 students enrolled in the eighth grade at UPT SPF SMP Negeri 47 Makassar when this research took place. Applying the purposive sampling technique, a total of 36 students from class VIII/4 were used for the sample. The researcher analyzed the data quantitively by using SPSS 25. According to the research's findings, the sample's mean score before treatment was 62.152, while the mean score after treatment was 83.333. The paired sample's two-tailed significance value was 0.00 < 0.05. We can conclude that the mind-mapping method used in the text twist game effectively improved students’ vocabulary.